Cara Cerdas Menyikapi Pandemi Covid-19 Dengan Mengurangi Belanja Sabun Cair Dengan Memanfaatkan Jeruk Purut dan Lerak - Astuti, Puji; Utami, Budhi; Puspita, Erna (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
Objective. Abstract A maximum of 250 English words with Times New he impact of the Covid-19 pandemic is still being felt by various sectors, even all levels of society. One of them is the Barokah Community Group (Pokmas Barokah), which is an association of housewives in Cerme Village, Grogol District, Kediri Regency. This community service activity aims to reduce one of the shopping posts for housewives, namely the purchase of soap for washing dishes by using kaffir lime and lerak. Many housewives in Pokmas Barokah have kaffir lime plants, but so far only use the leaves as an aromatic ingredient when cooking. The method of implementing the activities carried out by providing training and assistance in making soap. After the activity ended, housewives were able to make soap by using kaffir lime and lerak independently so that they could reduce their monthly expenses.